PEMBUKTIAN TINDAK PIDANA POLITIK UANG DALAM PEMILIHAN KEPALA DAERAH TAHUN 2019 - Ikhsan Bayanulloh; Fahmi Fajar Mustopa; Sarip Sarip; Nur Rahman (Jurnal De Jure Muhammadiyah Cirebon, 2021)
In almost every election event in Indonesia, it can be seen that there are many violations that often characterize it, the criminal behavior of money politics, for example, is always repeated even though the threat of criminal punishment lurks the perpetrators and recipients. This situation makes it difficult to enforce the law by the Panwaslu, the Police, and the Prosecutor's Office, which are members of the Gakkumdu center, this is because there are obstacles at the time of legal proof from the interpretation and perspective of the meaning of money politics itself which is considered to still have different views/perspectives. . The application of the law and the handling of violations by the Panwaskab against money politics based on formal offenses is a criminal act that has been committed and the act matches the formulation in Article 187 A paragraph (1) of Law Number 10 of 2016 concerning the Election of Governors, Regents and Mayors which requires an act that is prohibited or required to be completed without mentioning the consequences or prohibited by law is the act. Keywords: Crime, Money Politics, Pilkada.